Bibliographic collecting: historical context, terminology and research perspectives in Information Science - Santos Sundstrom, Admeire da Silva [UNESP]; Albuquerque, Ana Cristina de (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2020)
Bibliographic collecting is a practice that involves the gathering of bibliographic materials based on subjective issues. Research in that area seeks to understand the reasons underlying the pathologic, the documentary and the economic motivations related to the act of collecting; this implies the need for interdisciplinary studies. In this context, the question is: what is the state of the art of studies related to bibliographic collecting in the context of Information Science in Brazil? Thus, the core of this study is to present a theoretical and documentary understanding of studies related to bibliographic collecting. The paper also aims to address the terminology used, the main studies developed in the area and the prospects for carrying out new research in the subject. The method is bibliographic and bibliometric-documentary. We found that papers concerning bibliographic collecting were mainly published from the year 2000 on; however, it was only from 2007 on that we retrieved research documented in the proceedings of editions of the Encontro Nacional de Pesquisa em Ciencia da Infonnacao. The studies retrieved draw connections between Information Science, Museology, Social Memory, Psychology and Social Communication. We highlight the low incidence of studies focused on bibliographic collecting and the need for approaches that also contemplate bibliographic collecting in digital media.
Keywords: Bibliographic Collecting; Special collections; Bibliographic estate; Bibliophilia; Bibliomania